The Risk Management of Gold Pawn Product in Bank Syariah Indonesia (BSI) Krian Branch - Ahmad, Ardhi Seiva; Rohim, Ahmad Khoirur; Billah, Muhammad Arif; Fitrianto, Achmad Room (AL-QARDH, 2021)
The purpose of this research is to analyze the risk management of the BSI gold pawn product in the BSI Krian branch. This research is a qualitative research. In this research, the official of BSI Krian branch served as key informants which have a adequate knowledge about financing process BSI gold pawn. Data collection conducted through interview, documentation, and observation techniques. The result of this research shows that BSI Krian branch implements risk management on the BSI gold pawn product. There are four steps in the process of implementing risk management on the gold pawn product BSI Krian branch; risk identification, risk measurement, risk monitoring, and risk control. Besides implement risk management BSI Krian branch has prepared risk mitigation on the gold pawn product. The mitigation processes are to mitigate the miss gold estimation accuracy, the gold storage risk, the risk of payment failure or jamming, the last but not least is mitigate the gold price drop. In the implementation of risk management and risk mitigation by BSI Krian Branch there are two obstacles those are from internal and external banks. In the effort to face that obstacles, BSI Krian branch has had an effort to overcome both from internal and external banks. With the implementation of risk management on the gold pawn product by BSI Krian branch can prevent and minimize the risk which arise from that financing